2012
DOI: 10.1103/physreve.85.066309
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamic behavior of microscopic bubbles near a rigid wall

Abstract: The nonlinear dynamic behavior of microscopic bubbles near a rigid wall is investigated. Oscillations are driven by the ultrasonic pressure field that arises in various biomedical applications such as ultrasound imaging or targeted drug delivery. It is known that, when bubbles approach a blood-vessel wall, their linear dynamic response is modified. This modification may be very useful for real-time detection of bubbles that have found targets; in future therapeutic technologies, it may be useful for controlled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Dynamics of the acoustically excited bubbles are nonlinear and chaotic. These dynamics have been the subject of numerous experimental [1,15,[17][18][19][20] and numerical [21][22][23][24][25][26][27][28][29][30] studies . Achieving the full potential of bubbles in applications and understanding their role in the associated phenomena not only requires a detailed knowledge over their complex behavior but also on the effect of bubble oscillations on the propagation of acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics of the acoustically excited bubbles are nonlinear and chaotic. These dynamics have been the subject of numerous experimental [1,15,[17][18][19][20] and numerical [21][22][23][24][25][26][27][28][29][30] studies . Achieving the full potential of bubbles in applications and understanding their role in the associated phenomena not only requires a detailed knowledge over their complex behavior but also on the effect of bubble oscillations on the propagation of acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental minimum in acoustic response has been explained as due to a p phase shift in the bubble response at the fundamental resonance frequency (Leighton et al, 1996;Leighton et al, 1997;Zhang et al, 2012). The same phase shift has been noted in a theoretical analysis of sinusoidally forced small amplitude bubble oscillations (Suslov et al, 2012). The frequencies of these acoustic features are shown in this paper to provide unique estimators of bubble properties.…”
Section: Introductionmentioning
confidence: 82%
“…The regular perturbation linearization results in analytical expressions for steady fundamental and second harmonic induced oscillations of the bubble wall. It is well known that subharmonic and higher order harmonic resonance solutions of nonlinear forced oscillator models for bubble active acoustic response can also be found (Prosperetti, 1974;Francescutto and Nabergoj, 1983;Parlitz et al, 1990;Suslov et al, 2012). Indeed, it has been numerically shown that subharmonic oscillations are generated at lower forcing amplitudes than a second harmonic (Parlitz et al, 1990).…”
Section: Model Solution By Perturbation Methodsmentioning
confidence: 95%
“…Currently, researchers are studying the effects of bubbles with diameters of less than 100 m (i.e., microbubbles, Johnson and Cooke, 1981;Makuta et al, 2006;Dressaire et al, 2008;Suslov et al, 2012) on heat transfer, and expect a different effect from that of large bubbles (i.e., millimeter bubbles). The main questions over the use of such fine bubbles are the role of the high local number density of buoyant sources, and the effect of the interfacial tension that defines the rheological properties of the microbubble mixture (Llewellina and Manga, 2005).…”
Section: Introductionmentioning
confidence: 99%